Mid-term outcomes of right subaxillary approach versus median sternotomy incision for ventricular septal defect with patent ductus arteriosus - Zhi-Huang Qiu; Qing-Song Wu; Jun Xiao; Tian-Ci Chai; Mi-Rong Tang; Xian-Biao Xie; Dong-Shao Liao; Liang-Wan Chen (BMC, 2022)
Abstract Background This study aimed to evaluate and compare two surgical approaches to repair ventricular septal defect (VSD) with patent ductus arteriosus (PDA) and to explore the patients' health-related quality of life (HRQoL). Methods We conducted a retrospective study of all patients who had surgical repair of VSD and PDA between 2013 and 2015 using the right subaxillary approach (group A) or the median sternotomy incision (group B). The outcomes of both techniques were compared. Paediatric QoL Inventory 4.0 scale was applied to assess patients' HRQoL in the 6th postoperative year. Multiple linear regression analysis was performed to explore factors associated with higher HRQoL scores. Results A total of 128 patients were included (group A, n = 70 and group B, n = 58). Patients in group A were older and heavier than patients in group B. In group B, the diameters of VSD and PDA were larger and the pulmonary artery pressures were higher than those in group A (p < 0.001). No mortality occurred on a mean follow-up of 8.3 ± 1.2 years. Patients in group A had higher HRQoL scores than those in group B in terms of emotional and social functioning dimensions. The right subaxillary approach (OR: 3.56; 95% CI 1.65-5.46), higher parents' education level (OR: 1.62; 95% CI 0.65-2.31), and better family economic status (OR: 1.48; 95% CI 0.79-2.45) were associated with higher HRQoL scores. Conclusions Younger and smaller patients receiving median sternotomy incisions due to large defects and pulmonary hypertension had lower HRQoL scores. The right subaxillary approach, higher parents' education level, and better family economic status were associated with higher HRQoL scores.